Treatment of Mobile Phone Licences in the National Accounts - Maehle, Nils (IMF Working Papers; Working Paper, 2001)
The treatment of license payments in the national accounts has become increasingly important in recent years; with mobile phone licenses being auctioned for substantial values in several countries. Because the text of the System of National Accounts 1993 does not provide specific guidance on these licenses, their treatment needs to be decided on general principles. This paper concludes that there are usually two assets involved with mobile phone licenses, namely, the spectrum which is owned by the government, and the license which is an intangible nonproduced asset sold by the government to the licenseholder. The values of these two assets are linked complementarily. Alternative treatments of recording the license payments as sale of the spectrum itself, other taxes on production, production of a service, or rent, are considered and rejected. Methods of amortization of the license over its life are considered. An annex raises issues concerning the recognition of rights and obligations as assets and liabilities in national accounting.